Complexos Aril Substituídos de Rutênio (II): Síntese, Caracterização, Estudos de Fotoclivagem e Interação com DNA. - Abreu, Felipe Diógenes (2018)
In this study, three polypyridine complexes of ruthenium (II), [Ru (dppz) Naf]2+(1), [Ru (dppz) Ant]2+(2) and [Ru (Ant)3]2+(3) (dppz = dipyrido [ a: 2 ', 3'-c] phenazine, Naf and Ant are bipyridine ligand attached to a naphthyl and anthracenyl groups, respectively) were synthesized and characterized by UV-vis electronic spectroscopy, emission spectroscopy, IR, 1H NMR and cyclic voltammetry. DNA binding measurements carried out by electronic spectroscopy indicated from moderate ([Ru(Ant)3]2+, logKb=4.99) to strong ([Ru(dppz)Naf]2+, logKb=6.83) e [Ru(dppz)Ant]2+, logKb=6.78) intercalation binding. Competition assay monitored by fluorescence using selective groove-binders (methyl green and Hoechst) suggested both complexes 1 and 2 interact to DNA via minor groove. Additionally, these complexes exhibited moderate selectivity toward G-quadruplex DNA, which is likely due to the Naf and Ant pendant groups. Light-induced oxygen singlet production was measured using DPBF, which showed the quantum yield values (ΦΔ) followed the trend (3)+>(2)>[Ru(bpy)3]2+>(1)>[Ru(bpy)2dppz]2+. This result supports the key role of the pendant chromophoric groups Naf and Ant enabling the efficient production of 1O2. Important to remark, that an increase in the number of antracenyl pendant groups seemed to cause a large enhancement on the ΦΔ, particularly if comparing a singly modified complex [Ru(bpy)2Ant]2+ (ΦΔ= 0.74) and one triply modified [Ru(Ant)3]2+ (ΦΔ= 0.99). This behavior can be assigned to the efficiency of the triplet excited state of these complexes to convert triplet oxygen into singlet oxygen. Besides these metal complexes ability to photocleave DNA, even using a yellow LED, compounds 1 and 2 also showed great antibacterial activity using blue LED, particularly against Gram-positive bacteria. Altogether, these results indicated a new strategy to prepare enhanced light-activatable agents was successful opening new potential opportunities for their application in pharmacology and biotechnology.